Hydatic cyst of the cul-de-sac of Douglas. Vaginal treatment - Da Silva, Ema; Tarabochia, Carlos; Olalde, Carlos (Cirugía del Uruguay, 1990)
An observation of the unique hyaline pelvic hydatic cyst protruding in the cul-de-sac of Douglas is presented.